2016
DOI: 10.1111/jog.12990
|View full text |Cite
|
Sign up to set email alerts
|

Differences in autonomic neural activity during exercise between the second and third trimesters of pregnancy

Abstract: Aim: To test the hypothesis that autonomic neural activity in pregnant women during exercise varies according to gestational age. Methods: This cross-sectional study involved 20 healthy women in their second (n = 13) or third (n = 7) trimester of pregnancy. Incremental cardiopulmonary exercise testing was performed with an electromagnetic cycle ergometer. Heart rate variability was analyzed by frequency analysis software. Results: The low-frequency to high-frequency (LF/HF) ratio, an indicator of the sympathet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 56 publications
0
21
0
1
Order By: Relevance
“…Regarding aim 1, 99 tests (including 75 different protocols) were used to assess CRF,8 12 13 18 27–108 28 (including 16 different protocols) to assess muscular fitness,8 12 13 61 86 109–122 14 (including 13 different protocols) to assess flexibility,12 13 110 114 123–127 45 tests (including 40 different protocols) to assess balance,110 116 128–167 2 tests using the same protocol to assess speed168 169 and 3 tests using the same protocol were multidimensional 168–170. No results were found for other PF components such as agility or coordination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding aim 1, 99 tests (including 75 different protocols) were used to assess CRF,8 12 13 18 27–108 28 (including 16 different protocols) to assess muscular fitness,8 12 13 61 86 109–122 14 (including 13 different protocols) to assess flexibility,12 13 110 114 123–127 45 tests (including 40 different protocols) to assess balance,110 116 128–167 2 tests using the same protocol to assess speed168 169 and 3 tests using the same protocol were multidimensional 168–170. No results were found for other PF components such as agility or coordination.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 99 tests, a total of 75 corresponded to different protocols. For instance, there were 56 different protocols using a cycle ergometer, distributed as follows: only one article used the Arstila test68; one used the Bruce Protocol at 75% HR max 27; one applied the Modified Bruce ramp protocol at anaerobic threshold104; two employed the Modified Balke protocol at 70% HR max 34 41; one used a YMCA protocol;106 The remaining of articles (n=55) used ad hoc tests (ie, specifically designed for the purpose of the investigation); 11 of which32 37 38 41 45 57 64 79 107 used steady-state tests and 4428–31 33 35 36 39–41 43 44 46–56 59–63 65–69 90 100–106 108 171–173 used incremental tests. When analysing the type of test based on intensity, we found that 13 tests were maximal tests,31 43 44 47–49 59 60 67 103–105 171 37 submaximal tests29 30 35–40 42 45 46 50–52 54–57 62–66 68 69 79 90 100–102 106 108 172 and 3 used mixed tests28 33 41 containing submaximal and maximal stages within the same protocol.…”
Section: Resultsmentioning
confidence: 99%
“…Estes achados podem ser explicados, uma vez que o sistema nervoso autônomo atua constantemente para modular o funcionamento de vários sistemas orgânicos [5]. Assim, este sistema é o principal responsável pelo aumento da frequência cardíaca, que é mais elevada em mulheres no período gestacional a fim de suprir as alterações anatômicas e fisiológicas e garantir adequado aporte sanguíneo para o feto [1][2][3][16][17][18].…”
Section: Discussionunclassified
“…It is widely known that healthy pregnancy elicits adaptations in maternal haemodynamics via blood volume expansion, increased heart rate (HR), stroke volume (SV) and cardiac output (Q ̇) and decreased blood pressure (BP) and total peripheral resistance (TPR) (5)(6)(7)(8)(9). Furthermore, pregnancy induces a progressive change in the cardiac autonomic nervous system (ANS), with sympathetic nervous system activation and parasympathetic nervous system withdrawal (5,(10)(11)(12), consequently affecting maternal heart rate variability (HRV; 13,14). The majority of cardiac parameters influenced by pregnancy return to pre-pregnancy values postnatally (8,15).…”
Section: Introductionmentioning
confidence: 99%